If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10z + -10 + -3z + 3 = 0 Reorder the terms: -10 + 3 + 10z + -3z = 0 Combine like terms: -10 + 3 = -7 -7 + 10z + -3z = 0 Combine like terms: 10z + -3z = 7z -7 + 7z = 0 Solving -7 + 7z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7z = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 7z = 0 + 7 7z = 0 + 7 Combine like terms: 0 + 7 = 7 7z = 7 Divide each side by '7'. z = 1 Simplifying z = 1
| 5x+6=-x+6 | | 4x+y=24 | | -3.9a=31.2 | | x+2x-4x=12 | | 0.1x+0.7y=1.8 | | [5x+12]+81=0 | | -6x+4x-7x=0 | | -3x-5=4 | | x-2=x+4 | | 3n-5=-2(n-5) | | 0.1x+0.7=-1.8 | | 6q-2=3q | | (y-2)-(7y-9)= | | 9p-4p+6=7p-3p | | -0.454545455p=-8 | | -3(2x-4)-16=8x+3 | | 2x+8(7)=18 | | 2(0)+8(7)=18 | | 3x-5=3x-7 | | 6(2x+8)=4(3x-6) | | x(x+12)=108 | | 0.08x-0.01(50)=1.9 | | x+3(x+2)=46 | | 50x^2=2 | | x+12x=108 | | -38-2x=10-8x | | x+10x=24 | | 8.164=2(3.14)r | | (5x-1)4=x+6 | | 1fourthm=10 | | 8.164=2(3.14) | | 65-2x=10x+18 |